The relationship between adherence to treatment regimen and prayer in hemodialysis patients - Rambod, masoomeh; Sareban, mohammadtaghee; Pyravi, hamid; Kohan, mhmood (Advances in Nursing & Midwifery, 2011)
Abstract Background and aim Adherence is important for the health and well-being of patients on long-term hemodialysis therapy. Many factors such as spirituality and prayer have been hypothesized to have an effect on adherence in these patients. Therefore the aim of this study was to determine relationship between adherence and prayer in hemodialysis patients. Materials and methods A descriptive - corelational, cross-sectional design was used in this study. Two hundred patients with renal failure on hemodialysis, being treated at educational centers of Iran University of medical sciences, participated in the study. The subjects were selected by census method. Data were collected using the Adapted Prayer Scale (APS) based on Poloma and Pendleton’s (1991) prayer scale,a demographic form and reviewing medical charts. Validity of the questionnaire was determined by content validity method and reliability of this instrument was demonstrated by a Cronbach’s alpha (r = 0.8). The data were analyzed by SPSS-14. Findings overall patients had dietary and medication adherence (> 50%). But low of half had compliance to fluid restriction (44%). Many of them used prayer (62%). There were relationship between blood urea nitrogen and intra-dialytic weight gain with prayer p<0.05). But, prayer was not correlated with potassium and phosphorus (p>0.05). Conclusion this study indicated the association between dietary and fluid adherence with prayer. Therefore nursing practice and health worker for improving adherence and quality of life should be referred patient used prayer. Keywords: adherence, prayer, religion belief, Hemodialysis